TIME DELAY BETWEEN IMAGES OF THE LENSED QUASAR UM673 - Koptelova, E.; Chen, W. P.; Chiueh, T.; Artamonov, B. P.; Oknyanskij, V. L.; Nuritdinov, S. N.; Burkhonov, O.; Akhunov, T.; Bruevich, V. V.; Ezhkova, O. V.; Gusev, A. S.; Sergeyev, A. V.; et al. (Одеські астрономічні публікації, 2012)
We study brightness variations in the double lensed quasar UM673 (Q0142-100) with the aim of measuring the time delay between its two images. Methods.. We analyzed the V, R and I-band light curves of the A and B images of UM673, which cover ten observational seasons from August 2001 to November 2010. We also analyzed the time evolution of the difference in magnitudes (flux ratio) between images A and B of UM673 over more than ten years. We find that the quasar exhibits both short-term (with an amplitude of 0.1 mag in the R band) and long-term (with an amplitude of 0.3 mag) variability on timescales of about several months and several years, respectively. These brightness variations are used to constrain the time delay between the images of UM673. From a cross-correlation analysis of the A and B quasar light curves and an error analysis we measure a mean time delay of 89 days with an rms error of 11 days.